Macroeconomic Strategies and Policies Impacting the Decarburization of Economies in the Member Countries of the European Union - CIOBANU, Ghenadie; GROAZNICU, Luminița Popescu; RĂDUCANU, Dragoș; GOMBOS, Carol Cristina (European Journal of Sustainable Development, 2023)
In the context of the strategic development objectives of the European Union for the next strategic cycle until 2030, a priority issue is the decarburization of the economy, oriented towards the design and monitoring of strategies in order to achieve the objectives regarding climate change, the simultaneous stimulation of economic growth and ensuring social cohesion. A special place belongs to the progress of climate change, which requires progressive steps in the implementation of strategies and policies for all member countries of the EU. We propose in this article to focus on the application of decarburization strategies and policies in the countries of the European Union with an emphasis on Romania, with a necessary approach to social inclusion issues. The development of proposals for efficient strategies for the decarburization of economies in EU, the comparative analysis between the diversification of macroeconomic policies and instruments with different evaluation criteria, having as an essential support - the digitalization tools, which will accelerate the process of decarburization of the countries’ economy EU. We propose the development of decarburization strategies based on a mix of policies focused on establishing emission prices; standards and regulations; the implementation of capital, labor and innovation reallocation policies. Key words: Decarburization of the economy, strategies and policies, digitalization, innovation